Green Technology Accounting as an Innovation to Reduce Environmental Pollution - Sunarmin Sunarmin (Neraca : Jurnal Akuntansi Terapan, 2020)
The development of communication tools is part of the rapid development of information and communication technology. This change clearly influences communication patterns and relationships, for example in the field of work or business communication or organizational communication, education or learning communication, health communication, marketing communication primarily in marketing communication strategies, international communication, and others. Green accounting is a type of accounting that describes efforts to incorporate technology and environmental benefits and environmental costs into economic decision making or a financial outcome of a business. The aim is to find out whether green accounting technology can support the green movement of the business entity and the business continuity of the entity.This research is a descriptive study, using the library method where research is conducted by studying and collecting data from libraries related to tools, both in the form of journals and scientific studies of research that has been published in public journals.The results of the study concluded that the application of green technology and the impact of company activities need to be reported as a manifestation of corporate responsibility to stakeholders. The low awareness of reporting on environmental impacts is caused by several reporting constraints. The importance of environmental accounting needs to be done to improve green accounting technology that affects the positive value of environmental performance.